Micro-nano fiber with infrared and radar compatible stealth performance and application thereof
The electrospinning method of tin-doped zinc oxide micro-nanofibers and combined with heat treatment, the existing technology cannot meet the problem of infrared and radar compatible stealth, and the low infrared emissivity and microwave absorption performance of weapons and equipment are achieved, and the Battle and survivability.
Patent Information
- Application Number
- CN202410088251.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-22
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-01-22
AI Technical Summary
The existing stealth technology cannot meet the needs of weapons and equipment for infrared and radar-compatible stealth, and a single stealth method cannot effectively reduce the probability of targets being discovered, identified, tracked, positioned and attacked.
Made of tin-doped zinc oxide micro-nano fibers by electrospinning combined with heat treatment, it has a hollow fiber string spherical structure, chemical composition is Zn1-xSnxO, x=0.03-0.07, fiber diameter is between 100-400 nm, and ball diameter is between 800~1000nm, with superior low infrared emissivity and microwave absorption performance.
It has achieved low stealth performance of weapons and equipment in the infrared and radar bands, improved the combat capability and survivability of weapons and equipment, and met the current requirements for compatible stealth.
Smart Images

Figure CN119265752A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanofibers, and in particular to a micro-nano fiber with infrared and radar compatible stealth performance and application thereof. Background Art
[0002] Stealth technology mainly suppresses the target's energy emissions and detectable characteristic signals, reducing the probability of being discovered, identified, tracked, located and attacked, so as to protect itself from enemy attacks. Modern stealth technologies mainly include radar stealth, infrared stealth, laser stealth, visible light stealth, etc., but the above single stealth means can no longer meet actual needs. In order to improve the combat capability and survivability of weapons and equipment, infrared / radar compatible stealth materials have become the focus of research in countries around the world. Summary of the invention
[0003] In view of the above technical problems, the present invention provides a micro-nano fiber with infrared and radar compatible stealth performance and its application. The micro-nano fiber has excellent low infrared emissivity and microwave absorption performance, which can meet the requirements of compatible stealth of current weapons and equipment.
[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a micro-nano fiber with infrared and radar compatible stealth performance, which is made of tin-doped zinc oxide micro-nano fiber through electrospinning combined with heat treatment, wherein the chemical composition of the tin-doped zinc oxide micro-nano fiber is Zn 1-x Sn x O. The microscopic morphology is a hollow fiber-sphere structure, where x = 0.03-0.07, the fiber diameter is 100-400 nm, and the sphere diameter is 800-1000 nm.
[0005] Optionally, the chemical composition of the tin-doped zinc oxide micro-nano fibers is Zn 0.95 Sn 0.05 O.
[0006] In the present invention, when x=0.05, the tin-doped zinc oxide micro-nano fiber has low infrared emissivity of 0.549 and 0.648 in the 3-5 μm and 8-14 μm infrared bands, respectively. At the same time, when x=0.05, when the matching thickness of the tin-doped zinc oxide micro-nano fiber is 2 mm, the minimum reflection loss value at 8.6 GHz is -32.0 dB, the absorption frequency below -10 dB is 7.7-9.4 GHz (representing the frequency range that can absorb 90% of the energy electromagnetic waves), and the bandwidth is 1.7 GHz, indicating that the tin-doped zinc oxide micro-nano fiber has excellent microwave absorption performance (radar). In summary, the tin-doped zinc oxide micro-nano fiber of the present invention has superior low infrared emissivity and microwave absorption performance, which can meet the requirements of compatible stealth for weapons and equipment at this stage, and is a new type of infrared / radar compatible stealth material.
[0007] In a second aspect, the present invention also provides a method for preparing the above-mentioned micro-nano fibers, comprising the following steps: Step 1, adding zinc acetate and tin chloride to anhydrous ethanol and mixing evenly, then adding a mixed solution of polyvinyl pyrrolidone and N,N-dimethylformamide, stirring for at least 24 hours to obtain a precursor solution; Step 2, the precursor solution is electrospinned to obtain precursor fibers, wherein the electrospinning parameters are: at room temperature, voltage 15-17 kV, needle inner diameter 0.5 mm, solution advancement rate 0.1-0.2 mm / min, and distance between needle and receiver 10-15 cm; Step 3: Dry the precursor fiber and then heat it at 10-20°C min in air. -1 The temperature is raised to 600-700°C at a heating rate of 100°C, calcined for at least 2 hours, and naturally cooled to room temperature to obtain the product.
[0008] The micro-nano fiber preparation process of the present invention is simple and economical, and can be used as a functional filler in a coating to be coated on the surface of equipment and weapons, so that the weapons and equipment have infrared and radar compatible stealth performance, greatly improving the combat capability and survivability of the weapons and equipment.
[0009] In the present invention, the precursor fiber is heated at 10-20°C·min -1 The heating rate is raised to 600-700°C, which can completely decompose the impurities in the organic solvent and inorganic salt in the micro-nano fibers, and obtain micro-nano fibers with a hollow fiber string ball structure that are free of impurities and of high quality.
[0010] When the calcination temperature is too low (less than 600°C), the impurities in the organic solvent and inorganic salt in the micro-nano fibers are not completely decomposed, and the obtained micro-nano fibers contain impurities, which in turn affects their performance.
[0011] When the calcination temperature is too high (greater than 700℃) and the heating rate is greater than 20℃·min -1 , resulting in the fusion of the micro-nano fiber grains and the destruction of the micro-nano fiber structure, which causes the morphology of the hollow fiber string ball structure to be changed, so the calcination temperature is selected to be 600-700°C.
[0012] When the heating rate is less than 10℃·min -1 Or greater than 20℃·min -1 , the morphology of the hollow ball structure of micro-nano fibers cannot be obtained or maintained, so the heating rate is selected to be 10-20℃·min -1 .
[0013] Optionally, the zinc acetate is zinc acetate dihydrate; and the tin chloride is tin chloride dihydrate.
[0014] Optionally, the molar ratio of zinc acetate dihydrate to tin chloride dihydrate is (13-32):1, preferably (19-32):1.
[0015] The mass ratio of the N,N-dimethylformamide to polyvinyl pyrrolidone is (1-2):1, preferably 1:1.
[0016] The zinc acetate dihydrate and tin chloride dihydrate account for 5% to 10% of the mass of the precursor solution, preferably 5%.
[0017] Optionally, the inner diameter of the needle is 0.5 mm; the solution advancement rate is 0.1-0.15 mm / min, and the distance between the needle and the receiving plate is 12-15 cm.
[0018] In a third aspect, the present invention also provides an equipment with infrared / radar compatible stealth performance, the surface of the equipment is coated with a coating having the above-mentioned micro-nano fibers or the micro-nano fibers obtained by the above-mentioned preparation method added as functional fillers, in which the amount of the micro-nano fibers added to the coating accounts for 4% to 8% of the mass of the coating.
[0019] The present invention coats a coating with micro-nano fibers as functional fillers on the surface of weapons and equipment, so that the weapons and equipment have both infrared and radar stealth performance, greatly improving the combat capability and survivability of the weapons and equipment, and having military strategic significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Zn in Example 2 0.95 Sn 0.05 XRD spectrum of O micro-nanofibers; Figure 2 is Zn in Example 2 0.95 Sn 0.05 O SEM images of micro-nanofibers; Figure 3 To match the reflection loss curve of the product obtained in Example 2 with a thickness of 2 mm. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0022] Example 1 The present invention provides a method for preparing micro-nano fibers, comprising the following steps: Step 1: Add analytically pure zinc acetate (CH 3 COO 2 Zn·2H 2 O and analytically pure tin chloride SnCl 2 ·2H 2 O was added to anhydrous ethanol and mixed evenly, and then the organic solution was added and stirred for 24 hours to obtain a precursor solution, wherein (CH 3 COO 2 Zn·2H 2 O and SnCl 2 ·2H 2 O accounts for 5% of the mass of the precursor solution; the organic solution is obtained by mixing polyvinyl pyrrolidone (PVP) and N,N-dimethylformamide in equal mass ratios.
[0023] Step 2: Add the precursor solution into the syringe, and perform electrospinning at a voltage of 17 kV, a needle inner diameter of 0.5 mm, a solution advancement rate of 0.1 mm / min, and a distance between the needle and the receiver of 15 cm to obtain the precursor fiber.
[0024] Step 3: Place the precursor fiber in a constant temperature drying oven and dry it at 90 °C for 12 h. Then place it in an intelligent temperature-controlled box-type resistance furnace and heat it at 20 °C min in an air atmosphere. -1 The temperature was raised to 600 °C at a heating rate, calcined for 2 h, and naturally cooled to room temperature to obtain Zn 0.93 Co 0.07 O micro-nano fibers.
[0025] Example 2 The present invention provides a method for preparing micro-nano fibers, comprising the following steps: Step 1: Add analytically pure zinc acetate (CH 3 COO 2 Zn·2H 2 O and analytically pure tin chloride SnCl 2·2H 2 O was added to anhydrous ethanol and mixed evenly, and then the organic solution was added and stirred for 24 hours to obtain a precursor solution, wherein (CH 3 COO 2 Zn·2H 2 O and SnCl 2 ·2H 2 O accounts for 8% of the mass of the precursor solution; the organic solution is obtained by mixing polyvinyl pyrrolidone (PVP) and N,N-dimethylformamide in equal mass ratios.
[0026] Step 2: Add the precursor solution into the syringe, perform electrospinning at a voltage of 16 kV, a needle inner diameter of 0.5 mm, a solution advancement rate of 0.15 mm / min, and a distance of 12 cm between the needle and the receiver to obtain precursor fibers.
[0027] Step 3: Place the precursor fiber in a constant temperature drying oven and dry it at 90 °C for 12 h. Then place it in an intelligent temperature-controlled box-type resistance furnace and heat it at 15 °C min in an air atmosphere. -1 The temperature was raised to 650 °C at a heating rate, calcined for 2 h, and naturally cooled to room temperature to obtain Zn 0.95 Sn 0.05 O micro-nano fibers.
[0028] Example 3 The present invention provides a method for preparing micro-nano fibers, comprising the following steps: Step 1: Add analytically pure zinc acetate (CH 3 COO 2 Zn·2H 2 O and analytically pure tin chloride SnCl 2 ·2H 2 O was added to anhydrous ethanol and mixed evenly, and then the organic solution was added and stirred for 24 hours to obtain a precursor solution, wherein (CH 3 COO 2 Zn·2H 2 O and SnCl 2 ·2H 2 O accounts for 10% of the mass of the precursor solution; the organic solution is obtained by mixing polyvinyl pyrrolidone (PVP) and N,N-dimethylformamide in equal mass ratios.
[0029] Step 2: Add the precursor solution into the syringe, and perform electrospinning at a voltage of 15 kV, a needle inner diameter of 0.5 mm, a solution advancement rate of 0.2 mm / min, and a distance of 10 cm between the needle and the receiver to obtain the precursor fiber.
[0030] Step 3: Place the precursor fiber in a constant temperature drying oven and dry it at 90 °C for 12 h. Then place it in an intelligent temperature-controlled box-type resistance furnace and heat it at 10 °C min in an air atmosphere. -1 The temperature was raised to 700 °C at a heating rate, calcined for 2 h, and naturally cooled to room temperature to obtain Zn 0.97 Sn 0.03 O micro-nano fibers.
[0031] Comparative Example 1 Cobalt-doped zinc oxide nanofibers, chemical composition: Zn 0.96 Co 0.04 O, wherein analytically pure (CH 3 COO 2 Zn·2H 2 O and CO(NO 3 ) 2 6H 2 O as raw material, according to Zn 0.96 Co 0.04 O The appropriate amount of raw materials were weighed and mixed according to the stoichiometric ratio required. The mixed material was dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and polyvinylpyrrolidone (PVP) in equal mass ratio, and magnetic stirring was performed for 6 h to obtain a precursor solution, in which the mass fractions of PVP and metal salt were 6.5%, respectively. The precursor solution was loaded into a syringe with a stainless steel needle (model 23G), and the precursor Zn was prepared by electrospinning under the experimental conditions of a solution supply rate of 0.2 mL / h, a voltage of 20 kV, and a distance of 20 cm between the needle and the receiving plate. 0.96 Co 0.04 O / PVP fiber.
[0032] The precursor fibers obtained by electrospinning were dried and placed in an intelligent temperature-controlled resistance furnace at 1°C min -1 The temperature was raised to 600℃ and calcined for 2h, and then cooled to room temperature to obtain the target product Zn 0.96 Co 0.04 O nanofibers. For details, please refer to the paper ([1] Wang Xinkun, Zhao Fang, Wang Jianjiang. Zn 1-x Co x Electrospinning preparation of O nanofibers and their microwave absorption properties[J]. Journal of the Chinese Ceramic Society, 2020, 48(02): 161-168. DOI: 10.14062 / j.issn.0454-5648.20190376).
[0033] Comparative Example 2 Sn 0.84 Sm 0.08 Sb 0.08 O 2 Micro-nanofibers, SnCl2 ·2H 2 O、Sm(NO 3 ) 3 6H 2 O、SbCl 3 As raw material, according to Sn 0.84 Sm 0.08 Sb 0.08 O 2 Weigh an appropriate amount of raw materials in a stoichiometric ratio and dissolve them in anhydrous ethanol to obtain solution A. At the same time, polyvinyl pyrrolidone (PVP) was dissolved in an equal mass of N, N-dimethylformamide (DMF) to obtain solution B. Then, solutions A and B were mixed and stirred for 12 hours to prepare spinning precursor solution C. Solution C was transferred into a syringe with a stainless steel needle for electrospinning. Spinning parameters Wang Wei: temperature 25°C, humidity 50%RH, voltage 20kV, spinning needle model 21G, distance between needle and receiver 20cm, solution propulsion speed 0.1mL / h, receiving speed 140r / min.
[0034] The precursor body odor nanofibers prepared above were first placed in a vacuum drying oven at 100°C for 12 h, and then placed in an intelligent temperature-controlled box-type resistance furnace at 1°C min -1 The temperature was raised to 600 °C at a rate of 1.5 ℃, calcined for 2 h, and then cooled to room temperature to obtain the target product Sn 0.84 Sm 0.08 Sb 0.08 O 2 Micro-nano fibers. For details, please refer to the paper ([2] Xia Yuanjia, Zhao Fang, Li Zhizun, etc. Sn 1-x-y Sm x Sb y O 2 Preparation of micro-nano fibers and their infrared and laser compatible stealth properties [J / OL]. Journal of the Chinese Rare Earth Society).
[0035] Comparative Example 3 Compared with Example 2, this comparative example (CH 3 COO 2 Zn·2H 2 O and SnCl 2 ·2H 2 The molar ratio of O is 10:1, and the rest of the preparation method and the amount of raw materials are the same as in Example 2.
[0036] Comparative Example 4 Compared with Example 2, this comparative example (CH 3 COO 2 Zn·2H 2 O and SnCl 2 ·2H 2The molar ratio of O is 35:1, and the rest of the preparation method and the amount of raw materials are the same as in Example 2.
[0037] Comparative Example 5 Compared with Example 2, the voltage of electrospinning in this comparative example is 18 kV, the solution propulsion rate is 0.3 mL / h, the distance between the needle and the receiver is 18 cm, and the rest of the preparation method and raw material dosage are the same as in Example 2.
[0038] Comparative Example 6 Compared with Example 2, the heating rate of this comparative example is 3℃·min -1 The rest of the preparation method and raw material dosage are the same as in Example 2.
[0039] Comparative Example 7 Compared with Example 2, the heating rate of this comparative example is 50℃·min -1 The rest of the preparation method and raw material dosage are the same as in Example 2.
[0040] Comparative Example 8 Zn 0.96 Ce 0.04 O nanofibers were made of analytically pure (CH 3 COO 2 Zn·2H 2 O solution and Ce(NO 3 ) 3 6H 2 O solution as raw material, according to the molecular formula Zn 0.96 Ce 0.04 The raw materials were weighed and mixed in the required stoichiometric ratio. The mixed material was dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and polyvinylpyrrolidone (PVP) in an equal mass ratio, and magnetically stirred for 6 hours to obtain a precursor solution.
[0041] The precursor solution was loaded into a syringe with a stainless steel needle (model 23G) and electrospun to prepare the precursor Zn at a solution supply rate of 0.2 mL / h, a voltage of 20 kV, and a distance of 20 cm between the needle and the receiving plate. 0.96 Ce 0.04 O / PVP fiber.
[0042] The precursor fibers obtained by electrospinning were dried and placed in an intelligent temperature-controlled box-type resistance furnace at 1°C min -1 The temperature was raised to 600℃ and calcined for 2h, and then cooled to room temperature to obtain the target product Zn 0.96 Ce 0.04 O nanofibers. For details, please refer to the paper ([3] Wang Xinkun, Zhao Fang, Wang Jianjiang. Zn 1-x Ce xElectrospinning preparation of O nanofibers and their infrared radar compatible stealth performance[J]. Materials Review, 2019, 33(S2): 83-88).
[0043] Verification Example 1 1. In order to better illustrate the characteristics of the tin-doped zinc oxide micro-nano fibers prepared in the present invention, the tin-doped zinc oxide micro-nano fibers prepared in Example 2 were subjected to XRD and SEM analysis.
[0044] Figure 1 is Zn in Example 2 0.95 Sn 0.05 XRD spectrum of O micro-nanofibers; Figure 1 It can be seen that diffraction peaks were observed at (100), (002), (101), (102), (110) and (103), which is consistent with JCPDS card No. 36-1451. No other diffraction peaks were observed in the spectrum, indicating that the product is pure and its chemical composition is Zn 0.95 Sn 0.05 O, impurity content is below the detection limit.
[0045] Figure 2 is Zn in Example 2 0.95 Sn 0.05 SEM photos of O micro-nano fibers, where a, b, c, and d are SEM photos at different magnifications. Figure 2 It can be seen that Zn 0.95 Sn 0.05 The morphology of the ZnO micro-nano fiber is a micro-nano hollow fiber string ball structure, with a fiber diameter of 100-400 nm and a ball diameter of 800-1000 nm. 0.95 Sn 0.05 The hollow fiber ball structure of O micro-nano fibers is cross-linked to form a three-dimensional conductive network, which can effectively reduce the resistivity and thermal conductivity, thereby reducing the infrared radiation. 0.95 Sn 0.05 O micro-nano fibers have lower infrared emissivity; at the same time, the Zn 0.95 Sn 0.05 The hollow fiber string ball structure of O micro-nano fiber will also cause multiple reflections of the incident electromagnetic wave, resulting in resonance loss, which enhances the attenuation of the incident electromagnetic wave, making Zn 0.95 Sn 0.05 O micro-nano fibers have good electromagnetic wave absorption properties.
[0046] 2. The infrared emissivity of the products obtained in Examples 1 to 3 and Comparative Examples 2 to 8 was analyzed. The results are shown in Table 1.
[0047] Table 1 Infrared emissivity of the products obtained in Examples 1 to 3 and Comparative Examples 2 to 8 in the infrared bands of 3 to 5 μm and 8 to 14 μm
[0048] It can be seen from Table 1 that compared with the infrared emissivity of the products obtained in Comparative Examples 2 to 8, the products obtained in Examples 1 to 3 have lower infrared emissivity.
[0049] 3. The wave absorbing properties of the products obtained in Example 2 and Comparative Examples 1 and 8 were analyzed. The results are shown in Table 2.
[0050] Table 2 Reflection loss values of the products obtained in Example 2 and Comparative Examples 1 and 8 at a matching thickness of 2 mm
[0051] It can be seen from Table 2 that compared with the reflection loss values of the products obtained in Comparative Examples 1 and 8, the product obtained in Example 2 has a lower reflection loss value.
[0052] Figure 3 The reflection loss curve of the product obtained in Example 2 is matched with a thickness of 2 mm. Figure 3 It can be seen that when the matching thickness is 2 mm, Zn 0.95 Sn 0.05 The minimum reflection loss of ZnO micro-nano fibers is -32.0 dB at 8.6 GHz, the absorption frequency below -10 dB is 7.7-9.4 GHz (representing the frequency range that can absorb 90% of the energy of electromagnetic waves), and the bandwidth is 1.7 GHz. 0.95 Sn 0.05 O Micro-nano fibers have excellent microwave absorption properties (radar).
[0053] The tin-doped zinc oxide micro-nano fibers of the present invention have excellent low infrared emissivity and microwave absorption performance, which may be due to: the Zn 0.95 Sn 0.05 The hollow fiber ball structure of O micro-nano fibers is cross-linked to form a three-dimensional conductive network, which can effectively reduce the resistivity and thermal conductivity, thereby reducing the infrared radiation. 0.95 Sn 0.05 O micro-nano fibers have lower infrared emissivity; at the same time, the Zn 0.95 Sn 0.05 The hollow fiber string ball structure of O micro-nano fiber will also cause multiple reflections of the incident electromagnetic wave, resulting in resonance loss, which enhances the attenuation of the incident electromagnetic wave, making Zn 0.95 Sn 0.05 O micro-nano fibers have good electromagnetic wave absorption properties.
[0054] In summary, the tin-doped zinc oxide micro-nano fiber of the present invention has excellent low infrared emissivity and microwave absorption performance, which can meet the requirements of current weapons and equipment for compatible stealth, and is a new type of infrared / radar compatible stealth material.
[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A micro-nano fiber with infrared and radar compatible stealth performance, characterized in that: The micro-nano fiber is made of tin-doped zinc oxide micro-nano fiber through electrostatic spinning combined with heat treatment, wherein the chemical composition of the tin-doped zinc oxide micro-nano fiber is Zn 1-x Sn x O. The microscopic morphology is a hollow fiber-sphere structure, where x = 0.03-0.07, the fiber diameter is 100-400 nm, and the sphere diameter is 800-1000 nm.
2. The micro-nano fiber with infrared and radar compatible stealth performance as claimed in claim 1, characterized in that: The chemical composition of the tin-doped zinc oxide micro-nano fiber is Zn 0.95 Sn 0.05 O.
3. A method for preparing micro-nano fibers as claimed in claim 1 or 2, characterized in that: The following steps are involved: Step 1, adding zinc acetate and tin chloride to anhydrous ethanol and mixing evenly, then adding a mixed solution of polyvinyl pyrrolidone and N,N-dimethylformamide, stirring for at least 24 hours to obtain a precursor solution; Step 2, the precursor solution is electrospinned to obtain precursor fibers, wherein the electrospinning parameters are: at room temperature, voltage 15-17 kV, needle inner diameter 0.5 mm, solution advancement rate 0.1-0.2 mm / min, and distance between needle and receiver 10-15 cm; Step 3: Dry the precursor fiber and then heat it at 10-20 °C·min in air. -1 The temperature is raised to 600-700 °C at a heating rate, calcined for at least 2 h, and naturally cooled to room temperature to obtain the product.
4. The preparation method according to claim 3, characterized in that: The zinc acetate is zinc acetate dihydrate; the tin chloride is tin chloride dihydrate.
5. The preparation method according to claim 4, characterized in that: The molar ratio of zinc acetate dihydrate to tin chloride dihydrate is (13-32):1; The mass ratio of N,N-dimethylformamide to polyvinyl pyrrolidone is (1-2):1; and / or The zinc acetate dihydrate and tin chloride dihydrate account for 5% to 10% of the mass of the precursor solution.
6. The preparation method according to claim 5, characterized in that: The molar ratio of zinc acetate dihydrate to tin chloride dihydrate is (19-32):1; The zinc acetate dihydrate and tin chloride dihydrate account for 5% of the mass of the precursor solution; and / or The mass ratio of the polyvinyl pyrrolidone to N,N-dimethylformamide is 1:
1.
7. The preparation method according to claim 3, characterized in that: The inner diameter of the needle is 0.5 mm; the solution advancing rate is 0.1-0.15 mm / min, and the distance between the needle and the receiving plate is 12-15 cm.
8. An infrared / radar compatible stealth device, characterized in that: The surface of the equipment is coated with a coating layer which adds the micro-nano fibers described in claim 1 or 2 or the micro-nano fibers obtained by the preparation method described in any one of claims 3 to 6 as functional fillers.
9. The infrared / radar compatible stealth equipment according to claim 8, characterized in that: In the coating, the amount of the micro-nano fibers added accounts for 4% to 8% of the coating mass.
Citation Information
Patent Citations
Preparation of tubular zinc stannate (ZnSnO3) material by using electrostatic spinning process
CN103757748A
Preparation method for SnO2 / ZnO compound micro-nano fibers and product thereof
CN107142556A
ZnSnO3-C composite nanofiber and preparation method thereof
CN111575835A
Manufacturing method of aluminum nitride nanofiber
KR101909495B1
Fabrication of ultra-fine metal oxide decorated hybrid carbon nanofibers by single-nozzle co-electrospinning method using a phase-separated mixed polymer solution
KR1020130075487A